2021
DOI: 10.1111/nhs.12882
|View full text |Cite
|
Sign up to set email alerts
|

The association between health status and job satisfaction among female workers: A nationwide cross‐sectional study

Abstract: The purpose of this study was to determine the job satisfaction among female workers in Korea and the association between health status and job satisfaction. The Korean Longitudinal Survey of Women and Families was used for this nationwide cross-sectional study. Data from 1570 female workers were analyzed to determine job satisfaction and examine the association between health status and job satisfaction, controlling for other variables such as personal characteristics, work attributes, job opportunities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The nurses’ intention to leave was substantially correlated with their working hours, with p -value = 0.001 and F = 7.784, and the intention to leave increased for nurses who worked 12 hours. This was supported by a study conducted in the United States by Bae [ 25 ], who found that longer weekly work hours increased nurse turnover, as turnover increased when nurses worked ≥12 hours. The salary level has a substantial correlation with the intention to leave ( p -value = 0.001, F = 7.462).…”
Section: Discussionmentioning
confidence: 66%
“…The nurses’ intention to leave was substantially correlated with their working hours, with p -value = 0.001 and F = 7.784, and the intention to leave increased for nurses who worked 12 hours. This was supported by a study conducted in the United States by Bae [ 25 ], who found that longer weekly work hours increased nurse turnover, as turnover increased when nurses worked ≥12 hours. The salary level has a substantial correlation with the intention to leave ( p -value = 0.001, F = 7.462).…”
Section: Discussionmentioning
confidence: 66%
“…In a study conducted by Lopes et al [ 40 ] with a sample of 300 professionals, the results corroborate those of this present study, as job satisfaction was considered a protective factor of mental health. Moreover, a study with 1570 female workers investigating job satisfaction and its association with health status concluded that the presence of depressive symptoms was related to job satisfaction, and that the higher the job satisfaction, the lower the female workers’ perception of depressive symptoms [ 41 ]. In this study, the psychological vulnerability was statistically significant as a vulnerability factor for depressive symptoms, corroborated by the results of the study of Østergaard et al [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also related to job attitudes, such as job satisfaction ( Lavy, 2014 ). Job satisfaction is related to mental health and quality of life ( Faragher et al, 2005 ; Ioannou et al, 2015 ; Bae, 2021 ). Regarding mental illness, attachment to the leader is related to followers’ burnout ( Lavy, 2014 ).…”
Section: Introductionmentioning
confidence: 99%